Comparison of oral diseases status and treatment needs between armed forces personnel and Karnataka police service in Bengaluru city - R Satish Chandar; Sailee P Patankar (Wolters Kluwer Medknow Publications, 2014)
Introduction: The dental needs of Indian Army personnel have been periodically assessed to aid planners in identifying the requirements for dental care resources and the best allocation of those resources to provide optimum treatment, whereas in Karnataka police service the personnel dental needs are neither assessed nor provided with treatment. Objectives: The aim was to assess and compare the oral health status and treatment need among personnel of Armed Forces of India in comparison with police services. Materials and Methods: Oral health status was assessed among 300 personnel each from Indian Army and Karnataka police service using WHO proforma (1997). Study was conducted at ASC, Pioneer and Madras Engineering Group and Centre Bangalore for Army personnel and in 3 rd and 4 th battalion Bangalore for Karnataka state Police services. Results: About 45.3% of police personnel suffered from dental caries when compared to 42.3% of army personnel. The decay, missing and filled teeth of the army personnel was found to be 1.30 ± 2.33, and that of police personnel was 1.71 ± 2.67. About 37 (12.3%) army personnel had bleeding gums, 122 (40.7%) had calculus and 4 (1.3%) with pocket 4-5 mm compared with 38 (12.7%) police personnel with bleeding gums, 116 (38.7%) had calculus, 16 (5.3%) with pocket 4-5 mm and 5 (1.7%) with pocket 6 mm or more. Conclusion: The prevalence of the oral diseases namely dental caries and periodontal diseases was relatively high in police personnel when compared to the army personnel.